Effects of Exogenous Ketones on Blood β-OHB and Glucose: A Systematic Review and Meta-Analysis. (14th June 2022) - Falkenhain, Kaja; Daraei, Ali; Forbes, Scott; Little, Jonathan
Abstract: Objectives: Exogenous ketone (monoester or salt) supplements are increasingly being employed for a variety of research purposes and marketed amongst the general public for their ability to raise blood beta-hydroxybutyrate (β-OHB). Emerging research suggests a blood glucose-lowering effect of exogenous ketones. Here, we systematically review and meta-analyze the available evidence of trials reporting on exogenous ketones and blood glucose. Methods: We searched 6 electronic databases on December 13, 2021 for trials of any length that reported on the use of exogenous ketones compared to a placebo. We pooled raw mean differences (MD) in (i) blood β-OHB and (ii) blood glucose using random-effects models, and explored differences in the effects of ketone salts compared to ketone monoesters. Publication bias and risk of bias were examined using funnel plots and Cochrane's risk-of-bias tool, respectively. Results: Twenty-eight trials including a total of 332 participants met inclusion criteria. There was no evidence for publication bias. Four trials were judged to be at low risk of bias with some concern for risk of bias in the remaining trials. Compared to placebo, consumption of exogenous ketones raised blood β-OHB (MD = 1.98 mM; 95% CI: 1.52 mM, 2.45 mM; P < 0.001) and decreased blood glucose (MD = −0.47 mM; 95% CI: −0.57 mM, −0.36 mM; P < 0.001) across the post-supplementation period of up to 300 minutes. Across both analyses, significantly greater effects were found following ingestion of ketone monoesters compared to ketone salts ( P < 0.001). Conclusions: Consumption of exogenous ketone supplements leads to acutely increased blood β-OHB and decreased blood glucose. Ketone monoesters exert a more potent β-OHB-raising and glucose-lowering effect as compared to ketone salts. Funding Sources: Michael Smith Foundation for Health Research (MSFHR) Scholar Award.